Study in the book History of Tabaristan by Ibn Esfandiar - Abad, jawad kadhim (Al-Adab Journal, 2020)
The history of Tabaristan is one of the important works that covered the news of this troubled region, which represented a major challenge to the authority of the Abbasid state, and this book acquires its importance as it talked about the hidden secrets of secrets that relate to Tabaristan and the families that ruled it from the Pound, whose reigns for Tabaristan went back to before Islam. Thus, this book covered two important stages of the history of this region, the first stage before Islam as well as the Islamic stage, which was marked by the arrival of the Alevis to power and their separation from the Abbasid state and the building of an independent state in this region, Ibn Esfandiar talked in details about the Alevi imams, and did not hide his admiration for them, as well as his brief talk about the Bondi family. Accordingly, it can be said that the history of Tabaristan is considered as the most important amongst the works in this regard, as it included a number of works that were absent in the board and had no effect except in this book.